2009
DOI: 10.1136/bcr.05.2009.1858
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis--late diagnosis in an adult patient

Abstract: We present a case of hemophagocytic lymphohistiocytosis (HLH) in a previously healthy 30-year-old woman. The patient presented with features consistent with HLH: persistent fever, neurological abnormalities, lymphadenopathy, anaemia, leucopoenia and markedly elevated serum lactate dehydrogenase and ferritin levels. Diagnosis was delayed for approximately 1 month beyond presentation. Once initiated on treatment, the patient rapidly improved and was discharged from the intensive care unit and subsequently sent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, given the broad range of differential diagnoses for non-specific symptoms such as fever, fatigue, and pancytopenia in an AIDS patient, and the rarity of HLH, especially in the context of HIV, the diagnosis of HLH attributed to secondary causes such as disseminated histoplasmosis is inevitably delayed. In a case presentation reported by Dawn and fellow colleagues, diagnosis of HLH was delayed in a previously healthy 30 year-old woman for a period of 1 month, resulting in progressive HLH and ultimately death despite initiation of therapy upon diagnosis [8] . In addition, a review of 22 histoplasmosis-associated HLH cases demonstrated that of the 7 patients that died, 4 expired prior to initiation of therapy, and the other 3 expired while on treatment with amphotericin B in addition to immunotherapy with intravenous immunoglobulin [1] .…”
Section: Discussionmentioning
confidence: 99%
“…However, given the broad range of differential diagnoses for non-specific symptoms such as fever, fatigue, and pancytopenia in an AIDS patient, and the rarity of HLH, especially in the context of HIV, the diagnosis of HLH attributed to secondary causes such as disseminated histoplasmosis is inevitably delayed. In a case presentation reported by Dawn and fellow colleagues, diagnosis of HLH was delayed in a previously healthy 30 year-old woman for a period of 1 month, resulting in progressive HLH and ultimately death despite initiation of therapy upon diagnosis [8] . In addition, a review of 22 histoplasmosis-associated HLH cases demonstrated that of the 7 patients that died, 4 expired prior to initiation of therapy, and the other 3 expired while on treatment with amphotericin B in addition to immunotherapy with intravenous immunoglobulin [1] .…”
Section: Discussionmentioning
confidence: 99%
“…reported the case of a patient in which the diagnosis of HLH was delayed for over a month [6]. This was further supported in a postmortem analysis of 107 critically ill patients, where HLH was found in 69 (64%) patients [7].…”
Section: Discussionmentioning
confidence: 72%
“…Due to the rarity of this disease, knowledge gaps have frequently resulted in misdiagnosis or delayed diagnosis. There have been reports where patients experienced prolonged hospitalization or clinical deterioration without a clear diagnosis before the possibility of HLH was raised [8,9]. HLH may simulate several conditions that cause fever, pancytopenia, liver function test abnormalities, or neurologic findings.…”
Section: Discussionmentioning
confidence: 99%